MODIFIKASI LAGU “RAYUAN PEREMPUAN GILA” DENGAN FORMAT REMIX PADA TIKTOK BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA TAHUN 2017 TENTANG PEMILIHAN UMUM: The Modification of “Rayuan Perempuan Gila” Song Into Remix Format on TikTok Platform Based on CopyrightAct Number 28 of 2014 - Zahran, Dhebilla Kamiliya; Desmayanti, Rakhmita (Faculty of Law, Universitas Trisakti, 2024)
Songs are objects protected by copyright, with the development of technology there can be copyright violations against songs, namely in the form of song modifications without the author's permission which have detrimental impacts. This research discusses violations of copyright law related to the modification of the song